Guiding Students to Pursue French: The Guidance Counsellor’s Perspective in the Decision to Continue FSL - McGregor, Jessica (Université d'Ottawa / University of Ottawa, 2016)
This exploratory case study investigated the role secondary school guidance counsellors believed they played in the course selection process, especially regarding the continuation of French as a second language (FSL). As new initiatives have been recently introduced to increase retention in all FSL programs throughout Ontario (OME, 2013a), this study also sought to identify the factors guidance counsellors believed contributed to students continuing (or not continuing) the study of FSL past the mandatory Grade 9 credit. The following research questions guided this study: (1) How do guidance counsellors describe the process of course selection, with regards to FSL in particular?; (2) How do guidance counsellors view their role in the course selection process?; and (3) What do guidance counsellors identify as factors that contribute to students continuing (or not continuing) the study of FSL past Grade 9? Individual semi-structured interviews were conducted with 14 guidance counsellors from 12 schools across one school board in Ontario. Analysis of the insights shared by guidance counsellors highlight the complexities of the course selection process, as well as the strategies and tools they each used to prepare students to make the most informed decisions regarding their course selection. When counselling students about continuing optional FSL courses after Grade 9, participants expressed that they would encourage the pursuit of FSL courses, if the topic was student initiated. Emerging evidence showed that core French and French immersion students were counselled differently, with the latter receiving more attention if they expressed a desire to leave the program. Finally, guidance counsellors identified a wide variety of reasons they believed affected retention and attrition rates at their schools, with the most common being for future employment purposes and not seeing the value in learning French.
Keywords: guidance counsellor; course selection; French as a second language; retention; attrition